The Effect of Short Term Adventure Based Outdoor Program on Decreasing The Stress Level of College Students - Karisman, Vicki Ahmad; Supriadi, Dedi (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
This study was aimed at recognizing the effect of short-term adventure activities on decreasing college students’ stress. The programs administered in this study were expected to be able to help the college students in managing and decreasing their level of stress. The level of stress might affect their live, for instance affecting their study. This study was an experimental research with one-group pre-test post-test design. The population of this study were 83 college students taking the outdoor and recreation program. The program was conducted within 6 months; once in a week with 2 hours per session. The instruments used in this study were Perceived Stress Scale, with reliability 0,871, and activities including hiking, outbound, and swimming. The data were gathered in 10 meetings that were processed by SPSS 20. The result showed that there was a significant effect of short-term adventure activities on decreasing college students’ stress. AbstrakTujuan penelitian ini untuk mengetahui dampak dari aktivitas petualangan jangka pendek terhadap pengurangan stress mahasiswa. Program penelitian ini diharapakan dapat membantu mahasiswa dalam mengurangi tingkat stress. Tingkat stress pada mahasiswa akan menentukan jalannya kehidupan mahasiswa. Salah satunya pada penyelesaian studi. Metode penelitian eksperimen digunakan dengan desain pretest and posttest group design. Populasi penelitian ini mahasiswa yang mengikuti program rekeasi dan outdoor dengan partisipan sebanyak 83 orang. Program dilakukan selama enam bulan, dilakukan seminggu sekali selama 2 jam.  Instrumen yang digunakan dalam penelitian ini Perceived Stress Scale, dengan tingkat reliabilitas sebesar 0,871. Aktivitas yang dilakukan meliputi, hiking, outbound dan berenang. Data dikumpulakan melalui 14 pertemuan diolah melalui SPSS 20. Hasil perhitungan menujukan bahwa terdapat pengaruh yang signifikan dari petualangan jangka pendek terhadap pengurangan stress pada mahasiswa.